2021
DOI: 10.1037/pas0000956
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the German version of the Forms of Self-Criticizing/Attacking and Self-Reassuring Scale (FSCRS).

Abstract: Self-criticism is significantly associated with a variety of mental health difficulties affecting vulnerability, presentation, progress, and recovery. In contrast, self-reassurance is associated with good mental health, psychological well-being, and beneficial physiological processes. The 22-item Forms of Self-Criticizing/Attacking and Self-Reassuring Scale (FSCRS) is an internationally used self-report questionnaire for measuring manifestation and changes in different types of self-criticism and self-reassura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 87 publications
1
8
0
Order By: Relevance
“…Recently, Halamová et al ( 2018 ) suggested a two‐factor model based on reviewing and analysing data from previous studies that used FSCRS, in particular for community samples. It is not clear, however, which of the two models are best suited for clinical samples (Biermann et al, 2021 ). We chose to use the original three factor version, since the dimension FSCRS‐Hated self, which is likely to be the most clinically relevant one, is missing in the two‐factor model.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Halamová et al ( 2018 ) suggested a two‐factor model based on reviewing and analysing data from previous studies that used FSCRS, in particular for community samples. It is not clear, however, which of the two models are best suited for clinical samples (Biermann et al, 2021 ). We chose to use the original three factor version, since the dimension FSCRS‐Hated self, which is likely to be the most clinically relevant one, is missing in the two‐factor model.…”
Section: Discussionmentioning
confidence: 99%
“…This result supports the previous findings of Sommers-Spijkerman et al [ 52 ] regarding the three-factor solution and rationale of the cognitive-evolutionary model [ 68 ]. In addition, the three-dimensional model provides a better fit than the unidimensional and bifactorial ones according to the results of the confirmatory factor analyses of the FSCRS in clinical and non-clinical samples [ 44 , 45 , 48 , 69 71 ]. This is in contrast with a large intercultural study which has shown that a two-factor model of RS and SC (combining IS and HS) had a superior fit, although the three-factor one was acceptable too [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, BPD and ED patients showed significant higher SC and lower RS levels than non-clinical participants, thus indicating that the FSCRS-SF is able to discriminate between clinical groups that are known to differ in these two variables. A range of disorders, which include BPD and ED, are associated with high SC and low RS [ 69 ], though further studies are needed to describe mechanisms through which SC works in these pathologies [ 6 ]. In the case of BPD, SC and self-invalidation [ 78 ] are terms that, without having the exact same meaning, have huge overlap.…”
Section: Discussionmentioning
confidence: 99%
“…The hated‐self is proposed to focus on aggressive self‐persecution to remove undesirable aspects of the self, while the inadequate‐self is proposed to dwell on inadequacies to self‐correct 33 . Both forms of self‐criticism negatively correlate with self‐esteem and life satisfaction and discriminate between clinical and non‐clinical populations 34,35 …”
Section: Introductionmentioning
confidence: 99%